Transnational relations and world politics - edited by Robert O. Keohane and Joseph S. Nye, Jr. (Harvard University Press, 1972)
"Written under the auspices of the Center for International Affairs, Harvard University." "The essays in this volume appeared in ... International organization ... vol. XXV, no. 3 (summer 1971)"